Kaposi’s Sarcoma-Associated Herpesvirus-Encoded Viral IL-6 (vIL-6) Enhances Immunoglobulin Class-Switch Recombination - Rosario, Santas A.; Santiago, Gabriel E.; Mesri, Enrique A.; Verdun, Ramiro E. (Frontiers in Microbiology, 2018)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is an oncogenic gamma-herpesvirus that causes AIDS-associated Kaposi sarcoma (KS) and several lymphoproliferative disorders. During the humoral immune response antigen-activated mature B cells acquire functional diversification by immunoglobulin heavy chain (IgH) class-switch recombination (CSR). CSR is initiated by activation-induced cytidine deaminase (AID) which targets highly repetitive switch (S)-regions to mediate DNA double-stranded breaks (DSBs) in the IgH locus facilitating intramolecular recombination. Here we show that in the context of cytokine stimulation, CSR is enhanced in murine B cells exposed only to replication-competent KSHV in an environment of KSHV infection, which coincided with elevated AID transcripts. Using murine splenic B cells and the mouse lymphoma CH12F3-2 CSR system, we identified that vIL-6, but not murine IL-6, increased class-switching, which correlated with upregulated AID expression. Together, these data suggest a regulatory role for KSHV vIL-6 in functionally modulating B cell biology by promoting CSR, which may in part explain how KSHV infection influences humoral immunity and affect KSHV pathogenesis.